2017
DOI: 10.1111/asap.12140
|View full text |Cite
|
Sign up to set email alerts
|

Political Identity, Type of Victim, and Hate Crime‐Related Beliefs as Predictors of Views Concerning Hate Crime Penalty Enhancement Laws

Abstract: Little empirical work exists examining predictors of support or opposition of hate crime penalty enhancement laws despite such laws remaining a socially and politically contentious issue. Grounded in legal and philosophical arguments concerning hate crime laws, we tested political identity, victim minority status, and hate crime‐related beliefs as predictors of perceptions concerning penalty enhancement laws for bias‐motivated crime. Jury‐eligible Texas community members (n = 382) participating in a community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 42 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…The second hypothesis was supported in that HCBS-SF subscale scores were in line with politically conservative versus liberal party affiliation. Our findings provide a quantitative extension of Cramer and colleagues ( 2017 ), who reported qualitative findings about hate crime related attitudes. Political conservatism was particularly linked to legal arguments against hate crime laws, whereas political liberalism was connected to negative views of hate crime perpetrators.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The second hypothesis was supported in that HCBS-SF subscale scores were in line with politically conservative versus liberal party affiliation. Our findings provide a quantitative extension of Cramer and colleagues ( 2017 ), who reported qualitative findings about hate crime related attitudes. Political conservatism was particularly linked to legal arguments against hate crime laws, whereas political liberalism was connected to negative views of hate crime perpetrators.…”
Section: Discussionsupporting
confidence: 82%
“…Second, a study examining the link between political orientation and support for hate crime law penalty enhancements highlight the importance of beliefs about hate crimes. Cramer and colleagues ( 2017 ) found that political conservatism was associated with less support for punishment aspects of hate crime laws. Further, the link between political conservatism and lack of hate crime law support was explained by narrative legal arguments such as hate crimes being treated as all other crimes.…”
Section: Measurement Of Hate Crime Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, political scientists have tapped these theories to examine how social identity shapes political attitudes and mobilization (Monroe, Hankin, and Van Vechten 2000; Kalin and Sambanis 2018). The resulting literature has become rich, increasingly sophisticated, and vast, including applications to policy-related beliefs (Conover 1984; Citrin, Reingold, and Green 1990; Kinder and Winter 2001; Schmermund et al 2001; Hurwitz, Peffley, and Mondak 2015; Cramer et al 2017; Cramer et al 2017), political participation (Leighley 1996; Greene 1999; Schildkraut 2005; Miller and Conover 2015; Achen and Bartels 2016), and even distinctive forms of political identity (Huddy 2001).…”
Section: Social Identity and Guns: Building Theorymentioning
confidence: 99%
“…Yet, while most states have enacted laws—in varying forms—to combat the negative consequences associated with hate crimes, public support for hate crime laws has been considerably more mixed (Cramer et al, 2017; Hart-Teeter, 1999a, 1999b; Johnson & Byers, 2003; Steen & Cohen, 2004). While estimates vary, prior research has indicated that roughly two-thirds to three-quarters of Americans are supportive of hate crime laws (Cramer et al, 2017; Hart & Teeter, 1999a, 1999b; Johnson & Byers, 2003; Steen & Cohen, 2004). This means that while most Americans agree that it is important to have hate crime laws, approximately one third of Americans still do not support such legislation.…”
Section: Introductionmentioning
confidence: 99%